2018
DOI: 10.18632/oncotarget.25794
|View full text |Cite
|
Sign up to set email alerts
|

xCT inhibition sensitizes tumors to γ-radiation via glutathione reduction

Abstract: About 3 million US cancer patients and 1.7 million EU cancer patients received multiple doses of radiation therapy (RT) in 2012, with treatment duration limited by normal adjacent tissue damage. Tumor-specific sensitization could allow treatment with lower radiation doses, reducing normal tissue damage. This is a longstanding, largely unrealized therapeutic goal. The cystine:glutamate exchanger xCT is expressed on poor prognosis subsets of most solid tumors, but not on most normal cells. xCT provides cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 77 publications
(85 reference statements)
5
41
0
Order By: Relevance
“…4). These results corroborate a very recent report of xCT-KO in a breast cancer cell (MDA-MB-231) xenografts (37). However, our ability to extract MiaPaCa-2 xCT-KO Matrigel cell plugs at the end of the experiment revealed that surprisingly, some of the injected xCT-KO cells had remained viable for more than 3 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…4). These results corroborate a very recent report of xCT-KO in a breast cancer cell (MDA-MB-231) xenografts (37). However, our ability to extract MiaPaCa-2 xCT-KO Matrigel cell plugs at the end of the experiment revealed that surprisingly, some of the injected xCT-KO cells had remained viable for more than 3 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Cysteine uptake plays an important role in cancer by maintaining redox balance, and numerous studies have shown the efficacy of xCT inhibition on tumor growth 36,148,149 . Importantly, a recent study revealed that xCT suppression acts synergistically with the immunotherapeutic agent anti-CTLA-4 150 .…”
Section: Therapeutic Applications From Amino Acid Metabolismmentioning
confidence: 99%
“…xCT was related to radioresistance in human breast cancer and mouse melanoma cell lines [93,94]. CD98 contributed to radioresistance in head and neck squamous cell carcinoma [95].…”
Section: Mtor-dependent Antioxidant Mechanism In Solidmentioning
confidence: 99%